Exploring the engagement behaviours of Smile4life practitioners: lessons from an evaluation of the national oral health improvement programme for people experiencing homelessness in Scotland - Laura Beaton; Andrea Rodriguez; Gerry Humphris; Isobel Anderson; Ruth Freeman (Frontiers Media S.A., 2024)
IntroductionSmile4life is Scotland's national oral health improvement programme for people experiencing homelessness, aimed at reducing oral health inequalities experienced by this population. This study forms part of an evaluation of how the Smile4life intervention was being implemented within Scottish NHS Boards. The aim was to investigate the influence of the Smile4life intervention upon the engagement behaviours of Smile4life practitioners.MethodsFocus groups were conducted with Smile4life practitioners, to provide an insight into how the Smile4life intervention affected their skills, attitudes and experiences while interacting with people experiencing homelessness and their services providers. A purposive sample of oral health practitioners, including dental health support workers, oral health promoters/educators, and oral health improvement coordinators working in three NHS Boards were invited to take part. One focus group was conducted in each of the three NHS Boards. The focus groups were audio-recorded and transcribed. The COM-B model of behaviour was used as a framework for analysis.ResultsEleven Smile4life practitioners took part in the focus groups. All had first-hand experience of working with the Smile4life intervention. The average focus group length was 67 min. Working on the Smile4life intervention provided the Smile4life practitioners with: (i) the capability (physical and psychological), (ii) the opportunity (to establish methods of communication and relationships with service providers and service users) and (iii) the motivation to engage with Third Sector homelessness services and service users, by reflecting upon their positive and negative experiences delivering the intervention. Enablers and barriers to this engagement were identified according to each of the COM-B categories. Enablers included: practitioners' sense of responsibility, reflecting on positive past experiences and success stories with service users. Barriers included: lack of resources, negative past experiences and poor relationships between Smile4life practitioners and Third Sector staff.ConclusionThe Smile4life programme promoted capability, provided opportunities and increased motivation in those practitioners who cross disciplinary boundaries to implement the Smile4life intervention, which can be conceptualised as "boundary spanning". Practitioners who were found to be boundary spanners often had a positive mindset and proactive attitude towards the creation of strategies to overcome the challenges of implementation by bridging the gaps between the NHS and the Third Sector, and between oral health and homelessness, operating across differing fields to achieve their aims.